ION CHANNEL TRPA1 IS A PROMISING THERAPEUTIC TARGET FOR TREATMENT OF PAIN - Evgeniya Beskhmelnitsyna; Mikhail Korokin; Tatyana Avtina; Olga Martynova; Ivan Varavin; Anton Tishin (Research Results in Pharmacology, 2015)
TRPA1 is an ankyrin receptor of TRP family. It is a non-selective, calcium-permeable cation channel that is highly expressed by a subset of small diameter sensory neurons with cell bodies in the dorsal root, trigeminal, nodose and jugular ganglia. In the last time information about the role of TRPA1 in pain and cold sensitivity, as well as in the formation and maintenance of inflammation is increasing in scientific literature. Given this information, the interest for search and study of pharmacological agents, which selectively blocked of TRPA1 and reduced the severity of pain and inflammation is increasing.